Experimental color encryption in a joint transform correlator architecture - Tebaldi, Myrian Cristina (2011)
We present an experimental color image encryption by using a photorefractive crystal and a joint transform correlator (JTC) architecture. We achieve the color storing by changing the illumination wavelength. One JTC aperture has the input image information corresponding to a determined color channel bonded to a random phase mask (object aperture), and the other JTC aperture contains the key code mask. The joint power spectrum is stored in a photorefractive crystal. Each color data is stored as a modulation of birefringence in this photosensitive medium. The adequate wavelength change produces a corresponding power spectrum modification that avoids image encryption cross talk in the read out step. An analysis in terms of the sensitivity of the photorefractive silenite crystal for different recording wavelengths is carried out. It should be highlighted that the multiplexed power spectrum shows neither the multiplexing operation nor the amount of stored information increasing the system security. We present experimental results that support our approach.